2016
DOI: 10.1111/jmp.12249
|View full text |Cite
|
Sign up to set email alerts
|

Urinary sex steroid hormone and placental leucine aminopeptidase concentration differences between live births and stillbirth of Bornean orangutans (Pongo pygmaeus)

Abstract: This is the first study reporting a change in urinary PLAP, E G, and PdG concentrations during orangutan stillbirth and live birth pregnancies. The findings will assist in developing pregnancy screening tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
1
1
0
1
Order By: Relevance
“…To date, a few studies in non-human animals have shown that LNPEP concentrations are higher during pregnancy in sheep (Atakisi et al, 2007), mice (Matsumoto & Mori, 1998), and orangutans (Kinoshita et al, 2017) which agrees with our results. In humans, it has been reported that maternal serum LNPEP levels are decreased in patients with hypertensive disorders, and gestational diabetes mellitus and can be used to predict pregnancy and perinatal mortality (Kozaki et al, 2001;Tian et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…To date, a few studies in non-human animals have shown that LNPEP concentrations are higher during pregnancy in sheep (Atakisi et al, 2007), mice (Matsumoto & Mori, 1998), and orangutans (Kinoshita et al, 2017) which agrees with our results. In humans, it has been reported that maternal serum LNPEP levels are decreased in patients with hypertensive disorders, and gestational diabetes mellitus and can be used to predict pregnancy and perinatal mortality (Kozaki et al, 2001;Tian et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, serum P-LAP level has been reported to be a viable predictor of fetal death (Tian et al, 2016). In female Bornean orangutans that gave stillbirths, the P-LAP concentration in urine failed to increase; whereas in those that gave live births, the average P-LAP concentration in urine showed a progressive increase till delivery (Kinoshita et al, 2017). P-LAP is believed to prevent the premature onset of uterine contractions by degrading oxytocin, thereby playing a role in the maintenance of normal pregnancy (Yamahara et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…。しかし,尿は排泄後に時間が経 過すると乾燥して回収できなかったり,排尿場所によっ ては全く回収ができない場合がある。そのため,より 採取が容易な糞を用いた研究が,その後 1990 年頃から 飼育下および野生下で発表されるようになった (Lasley and Kirkpatrick, 1991;Wasser et al, 1988;Ziegler et al, 1989) 。雌の性ホルモン(特に種特異性のない性ステロ イドホルモン)濃度を分析することで,春機発動(繁 殖能力の発現開始) ,発情期(排卵期) ,妊娠の有無, 陰部腫脹との関係などが明らかにされてきた (Carroll et al, 1990;Curtis et al, 2000;Dahl et al, 1987;Heistermann et al, 1996;Kinoshita et al, 2017;Shimizu, 2005;Shimizu et al, 2003) Fourie et al, 2016) Fairbanks et al, 2011;Henley et al, 2013;Vliegenthart et al, 2016;Yamanashi et al, 2013) (Maggioncalda et al, 1999;Marty et al, 2015) ,その間に成長ホルモンの濃度も上昇 することが確認されている (Maggioncalda et al, 2000) 。 ただし,野生オランウータンにおける遺伝解析により, アンフランジ(フランジがない)雄でも子の父親になっ ていることが確認されており (Goossens et al, 2006) (Prudom et al, 2007;Roberts et al, 2001;Soltis et al, 2005;Ziegler and Snowdon, 2000;Ziegler et al, 1996) (Woods, 1975) Pettitt et al, 2007) 。糞中の水分含量が高いと,より一層細菌による 代謝は活発になる (Palme, 2005 (Khan et al, 2002;Palme, 2005;Pettitt et al, 2007;Woods, 1975 (Kinoshita et al, 2016) 。オランウータンやチンパンジーにおいて, 有機溶媒を用いてフィルターペーパーからホルモンを 抽出し分析に成功している研究例もある (Seraphin et al, 2008;Shideler et al, 1995;Thompson and Knott, 2008) 。 このように,調査地の状況に合わせてどのような保存 方法をとるべきかについても,予備実験で確認してお くことが重要である。また,近年は「Field-Friendly 法」 として,保存過程を経ずに野外で直接サンプルからホ ルモンを抽出し実験室に抽出物を持ち帰って分析して い る 例 も あ る (Nugr...…”
unclassified